Urinary tract injuries in polytraumatized patients - (:unkn) unknown (SPRINGER, 2005)
Background. Within the S3 Guideline Project of the European Association of Urology (EAU) an expert committee was set up to develop guidelines for the appropriate management of genitourinary trauma. These European guidelines were accepted in principle as national guidelines by the German Urological Society. Therefore, they also became the basis of the contribution of the German Urological Society to the S3 Guideline Project Polytrauma of the German Society for Trauma Surgery. Method. For the guideline management of genitourinary traumaall the requirements for classification as S3 guidelines were fullfilled. The guideline itself was developed in accordance with the principles of evidence-based medicine A systematic analysis of literature published between 1966 and 2004 was carried out. The articles retrieved were assessed in respect of study design and clinical relevance and classified following the scheme of the Centre for Evidence-Based Medicine in Oxford. Conclusion. In suspected renal injuries the hemodynamic situation of the patient is the benchmark for the diagnostic and therapeutic algorithm. The diagnostic gold standard for the assessment of haemodynamically stable patients is CT scanning. Uncontrolled haemodynamic instability is an indication for immediate explorative laparotomy. Partial ureteral tears are managed by stenting; complete tears by immediate surgical repair. Pelvic fractures are often associated with bladder ruptures. Extraperitoneal bladder ruptures, identified by retrograde cystography, are in most cases safely managed by simple catheter drainage. Intraperitoneal ruptures require surgical intervention. Blood at the meatus may suggest a urethral lesion - blind urethral catheterization should not be attempted. Suprapubic cystostomy and delayed urethroplasty are recommended.
Keywords: polytrauma; renal injury; ureteral injury; bladder injury; urethral injury; BLUNT RENAL TRAUMA; SURGICAL-MANAGEMENT; URETHRAL INJURIES; BLADDER RUPTURE; EXPERIENCE; TOMOGRAPHY; DIAGNOSIS